Demographic and Clinical Patterns of Acute Otitis Media in a Secondary Care Setting - Sipahutar, Gabriella M.C.; Tarigan, Rita Febrina; Sipahutar, Nathalia E.R.; Sihombing, Jenny Ria (Empiricism Journal, 2025)
Acute Otitis Media (AOM) is an acute inflammation of the middle ear lasting less than three weeks and is a common condition in low-income countries such as Indonesia. Prompt and appropriate care is essential to prevent progression to more severe forms. This study aimed to describe the characteristics of AOM patients treated at the ENT Outpatient Clinic of Deli Serdang Lubuk Pakam Regional General Hospital in 2017. This was a descriptive cross-sectional study involving 102 AOM cases identified through total sampling at the ENT Outpatient Clinic of Deli Serdang Lubuk Pakam Regional General Hospital throughout 2017. The measured variables included age, gender, affected ear, chief complaint, treatment, and hearing impairment. Male patients accounted for 57.8% of cases, while females comprised 42.2%. Most patients were aged 0–5 years. The left ear was most affected (51.9%). The most frequent symptom was ear pain, reported in 36.3% of cases. All patients received medical treatment. Hearing impairment was observed in 54.9% of patients. Conclusion: AOM was most prevalent among male children aged 0–5 years. Ear pain was the most common presenting complaint. Medical therapy was the primary treatment modality, and over half of the patients experienced hearing impairment.